2020
DOI: 10.1021/acsami.0c06829
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Substoichiometric Electron Beam Patterned Bismuth Sulfide

Abstract: Direct patterning of thermoelectric metal chalcogenides can be challenging and is normally constrained to certain geometries and sizes. Here we report the synthesis, characterization, and direct writing of sub-10 nm wide bismuth sulfide (Bi2S3) using a single source, spin coatable, and electron beam sensitive bismuth(III) ethylxanthate precursor. In order to increase the intrinsically low carrier concentration of pristine Bi2S3, we developed a self-doping methodology in which 23 sulfur vacancies are manipulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…For example, Recatala-Gomez et al prepared a Bi 2 S 3 thin film via electron beam lithography with an electrical conductivity of 6 S cm À1 , which showed a low Seebeck coefficient (À21.41 mW K À1 ) at room temperature (RT). 37 This poor performance indicated that the process for the fabrication of the film and the carrier concentration need to be appropriately improved.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Recatala-Gomez et al prepared a Bi 2 S 3 thin film via electron beam lithography with an electrical conductivity of 6 S cm À1 , which showed a low Seebeck coefficient (À21.41 mW K À1 ) at room temperature (RT). 37 This poor performance indicated that the process for the fabrication of the film and the carrier concentration need to be appropriately improved.…”
Section: Introductionmentioning
confidence: 99%
“…The BiO peak in the O 1s region has also been observed to be sensitive to other factors, such as reduced metal content on the surface of the material. [ 18,36,37 ] At this time, the appearance of the peak at 532 eV in the O 1s region of the composites is attributed to the formation of interfacial BiO bonds between the Bi 2 S 3 and oxygen‐containing functional groups on the MWNT. Intensities at higher B.E.…”
Section: Resultsmentioning
confidence: 95%
“…Bi 2 S 3 possesses a large Seebeck (about 480 µV K −1 ) and surprisingly low κ, [ 16–18 ] however, its large electrical resistivity results in a low ZT value of ≈0.05 at room temperature. [ 5 ] On the other hand, CNTs have been widely used in composite TE materials in recent years, due to its excellent electrical conductivity, low dimensional nanoscale, and extraordinary thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most popular method to prepare thermoelectrics is to use conventional solid-state sintering that involves ball milling and/or spark plasma sintering (SPS), which is energy-consuming and lack of mechanisms to precisely control the size, shape and surface chemistry. In comparison with the top-down nanostructuring or nanopatterning such as electron beam lithography [71], the bottom-up approaches are relatively cost-effective and also offer advantages in controlling phase purity, crystallinity, density and dimensions. Nanostructured or nanocomposite thermoelectric materials can help enhance ZT via increasing power factor through modulation doping, decreasing thermal conductivity via phonon scattering [72], increasing S by modulating the density of states of carriers, and energy filtering which results in simultaneous increase in S and σ [73].…”
Section: Bottom-up Nanostructuring Of Thermoelectricsmentioning
confidence: 99%